Patterns for marking ingredients and order of processes in Costa Rican gastronomic texts - Hernández Delgado, Mario (2019)
In this paper, a synthesis of the procedures and results related to the first stage or pre-computational stage of the research project “Análisis de contextos definicionales en corpus de gastronomía tradicional en Costa Rica (CODEGAT)” [“Analysis of definitional contexts in corpora of traditional gastronomy in Costa Rica (CODEGAT)”] will be presented; in that stage, the linguistic resources for marking conceptual relations in gastronomic textual corpora in Costa Rican Spanish are studied. Specifically, the tasks for the identification of patterns associated with two types of features that were found as necessary in the formulation of a recipe (“ingredients” and “processes order”) will be explained, to finally propose a categorization of the markers that appear in such patterns, with typical examples of each class and of its possible contexts of appearance. Key Words: lexicography, semi-specialized lexicography, definitional patterns, definitional markers, lexical-semantic relations.